A Way to Improve Luminescent Efficiency of Bis-Chalcone Derivatives - Meng Guan Tay; Mee Hing Tiong; Ying Ying Chia; Suzie Hui Chin Kuan; Zhi-Qiang Liu (Journal of Chemistry)
Chalcone related compounds have been reported as a poor luminescence molecule due to the quenching processes from the intramolecular torsional motions and cis-trans isomerization in the α,β-unsaturated ketone moiety. Despite this limitation, we found a way to improve the luminescent efficiency of our bis-chalcone derivative. In this project, two series of bis-chalcone compounds have been synthesized through Claisen-Schmidt condensation by reacting terephthaldehyde or 2,5-dimethoxyterephthaldehyde with the respective R-acetophenone [where R = H (1a and 2a) and ortho-hydroxy (1b and 2b)] in 1 : 2 mole ratio. The presence of a methoxy (OMe) substituent on the central phenyl ring of bis-chalcone has weakened the C=C bond at the α,β-unsaturated ketone moiety of 2a and 2b. Interestingly, the OMe group has improved the emission efficiency of the bis-chalcone; that is, the quantum yield of 1a in DCM solution was not able to be determined due to poor luminescence, but the quantum yield of 2a in DCM solution was improved to 0.57. In addition, compound 2a also shows solvatochromism effect where the λmax emission shifted from 499 nm in nonpolar solvents (benzene) to 523 nm in polar solvents (acetonitrile). This work provides another way to improve the emission efficiency of chalcone related compounds apart from using the complexation method which has been reported before.